Bias current optimization of Wurtzite-GaN DDR IMPATT diode for high power operation at THz frequencies - Banerjee, Soumen; Mukherjee, Moumita; Banerjee, J. P. (International Journal of Advanced Science and Technology, 2010)
The properties and performance of DDR p+pnn+ Wurtzite Gallium Nitride (Wz-GaN) Impatt diodes at Terahertz (THz) frequencies has been investigated for optimum bias current density through modeling and simulation technique. A double iterative computer method based on drift-diffusion model has been used to study the DC and small signal admittance properties of the device. The bias current density is optimized with respect to maximum conversion efficiency and device negative resistance at both 0.3 and 0.5 THz frequencies. The simulation studies show that these devices are potential sources for generating high RF power. The DC-to-RF conversion efficiency of the device is found to be 12.3% and 11.4% at 0.3 THz and 0.5 THz at the optimum bias current density of 2 x 107 A/m2 and 1.8 x 108 A/m2 respectively. The design results presented in this paper will be useful to realize experimentally Wz-GaN IMPATTs for Terahertz frequencies.